Epidemiology of Cryptosporidium sp. infection among free-range and intensive farm birds in Akure South LGA, Ondo State, Nigeria - Olonisakin, Akinbode Ayekooto (2023)
The study showed that the applied fermentation and drying periods single handedly resulted in moisture content higher than the recommended, coupling 8 days fermentation with 6 days drying period resulted in a moisture content of 5.6% which falls below the acceptable standard (7.5%) recommended. Number of beans/100 g increased with increasing fermentation and drying periods. Coupling any of the fermentation periods with 5 or 6 days drying duration resulted in mould content within the acceptable grade 1 limit (3%). Longer fermentation period coupled with any of the drying durations resulted in very encouraging and minimal values of purple, while coupling 6, 7 or 8 days fermentation period with 6 days drying resulted in slaty content within the grade 1 limit (3%).